The dawn of photography in Costa Rica: 1848-1869. A documentary contribution - Brenes Tencio, Guillermo (2022)
The present article's purpose is to facilitate the scholars —national and foreigns—the consultation of twenty journal ads, useful to examinate the historic evolutionof the photography in Costa Rica between 1848 and 1869. The information givencomes from the following newspapers: Boletín Oficial, Crónica de Costa Rica, ElCostarricense, La Época, La Gaceta and La Nueva Era.